2000
DOI: 10.1176/appi.ajp.157.11.1806
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary Treatment of Eating Disorders

Abstract: This study suggests that a substantial minority of patients with severe eating disorders will not seek treatment unless legally committed to an inpatient program. Despite the involuntary initiation of treatment, the short-term response of the legally committed patients was just as good as the response of the patients admitted for voluntary treatment. Further, the majority of those involuntarily treated later affirmed the necessity of their treatment and showed goodwill toward the treatment process. Only a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 10 publications
0
93
0
7
Order By: Relevance
“…When comparing treatment duration between involuntary and voluntary patients, five out of seven studies reported significantly longer treatment durations for involuntary patients [14][15][16]18,22]. The type of involuntary treatment applied was also examined, with forced tube feeding used in four of the studies [17][18][19]23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing treatment duration between involuntary and voluntary patients, five out of seven studies reported significantly longer treatment durations for involuntary patients [14][15][16]18,22]. The type of involuntary treatment applied was also examined, with forced tube feeding used in four of the studies [17][18][19]23].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reviews of involuntary treatment have not focused specifically on the frequency, type and effect of involuntary treatment [11][12][13]. The review by Russell [13] provides an overview of ethical and legal aspects of involuntary treatment along with a brief summary of three studies published at the time [14][15][16]. The review by Thiel and Paul [11] is written in German and includes three studies published in English and one study published in German [14][15][16][17], with a brief English version published by Thiels [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El presente trabajo intenta mostrar que la dicotomía entre derechos a la "libertad" o a vigilancia permanente, apremio, pérdidas de la privacidad, intimidad y confidencialidad. El médico recurre al principio de beneficencia impulsado por la necesidad imperiosa de curar complicaciones peligrosas, y fundamentalmente salvar la vida a la anoréctica, aun cuando ella rechace la ayuda y deba imponérsela contra su voluntad [8][9][10][11][12] .…”
Section: Procedimientos De Decisiónunclassified
“…Por razões éticas, a efetividade do tratamento compulsório nessa área é difícil de ser avaliada na forma de estudos empí-ricos e impossível de ser realizada na forma de intervenções experimentais ou randomizadas. Não obstante controvérsia do tratamento compulsório em psiquiatria e os aspectos legais, há poucos estudos sobre a evolução dos pacientes internados com TA de maneira compulsória 15 . Um estudo sugeriu que o tratamento compulsório em adultos possa não ser efetivo em alcançar os efeitos desejáveis a longo prazo, apesar de a curto prazo os pacientes internados sem consentimento próprio alcancem o peso esperado 32 .…”
Section: A Resistência Ao Tratamento E O Internamento "Compulsório"unclassified